2016
DOI: 10.1186/s12884-016-0994-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival of neonates and predictors of their mortality in Tigray region, Northern Ethiopia: prospective cohort study

Abstract: BackgroundNeonatal mortality accounts for an estimated 2.8 million deaths worldwide, which constitutes 44 % of under-5-mortality and 60 % of infant mortality. Neonatal mortality predictors vary by country with the availability and quality of health care. Therefore, aim of this study was to estimate survival time and identify predictors of neonatal mortality in Tigray region, northern Ethiopia.MethodA prospective cohort study design was carried out among a cohort of neonates delivered in seven hospitals of Tigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
116
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(157 citation statements)
references
References 30 publications
35
116
6
Order By: Relevance
“…The mortality rate of premature infants born at home is five times as high as those at the same hospital supported by studies conducted in Johannesburg, South Africa [18,28] and Jimma, Ethiopia [8].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mortality rate of premature infants born at home is five times as high as those at the same hospital supported by studies conducted in Johannesburg, South Africa [18,28] and Jimma, Ethiopia [8].…”
Section: Discussionmentioning
confidence: 97%
“…Studies reported that preterm neonatal mortality in Ethiopia there is regional variation 28.28% University of Gondar [7], Tigray region Northern Ethiopia 34% [8], and Jimma University Specialized Hospital, Ethiopia 34.9% [9], 47% rural Ethiopia [10], 63% Northern Ethiopia [11]. According to different kinds of literature, factors that are associated with preterm neonatal mortality include;…”
Section: Introductionmentioning
confidence: 99%
“…The study included 1162 mother-neonate dyads. Details of sample size calculation and sampling procedure have been published previously [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Clinical characteristics related to the mother and her baby were either extracted from medical record or collected at baseline. Details of follow up have been published previously [20]. …”
Section: Methodsmentioning
confidence: 99%
“…To assess the association of neonatal sepsis with neonatal mortality, we have include five studies [33,[36][37][38]41], Patients who had neonatal sepsis had almost one and half times higher chance of neonatal death compared to those patients without sepsis OR: 1.23(95% CI:1.1, 1.4) ( Figure 7). The heterogeneity test showed extreme evidence of variation across studies (I 2 = 90%, P=…”
Section: Neonatal Sepsismentioning
confidence: 99%